Gibbs energy approach for aqueous processeswith HF, HNO3, and CO2–CaCO3 - Chiavone Filho, Osvaldo (2004)
Chemical thermodynamic calculations were used to represent vapor–liquid equilibriaand chemical equilibria for aqueous systems with HF, HNO3, and CO2–H2O–CaCO3solutions. The entropy production related to the dissolution reaction of calcite wascalculated using multiphase thermodynamics and experiments carried out in this work.Modern simulation methods combined with experiments provide a useful tool for theresearch and design of new processes as well as evaluating changes in the operationalconditions of chemical processes. These methods are used to study metallurgical, pulp,and paper industrial processes that involve the presented aqueous solutions